The Garden, the Island and the Myth. An ethnography of Indianness in Guadeloupe and of a circulation of plants and knowledges (West Indies, Mascarene Islands) - Lou Kermarrec (Nuevo mundo - Mundos Nuevos, 2025)
This text is an abridged version of the introduction to my doctoral thesis in Anthropology and Ethnobotany. The thesis analyses at the transmission of plant-related ecological knowledge in the context of the migration of Indian indentured labourers (1834-1917) to the Creole-speaking islands of the West Indies and Mascarene. The environmental aspect of these migrations is an invisible part of academic research, as is the question of the interdependence between plants, gods, myths and Hindu cults practised in these islands today. Using Guadeloupe as a case study, this thesis analyses the ways in which plants and their uses have been passed down through families of Indian origin, since the days of indentured labour. The thesis also examines how these plants have spread across the landscape of the archipelago, over a long period of time. By mobilizing ethnographical, botanical and historical sources, I formulate hypotheses on the introduction of plants by Indian indentured labourers to Guadeloupe (19th century) and by their descendants (20th to 21st centuries). When the relationship between the garden and the plant landscape – whether real, mythological or imaginary – is placed within an extended chronology, it makes it possible to question and contextualise the existence of Indian knowledge in the Creole Garden, as well as the existence of an Indianness (indianité) in Guadeloupe, often understood as the expression of a particular identity. The practice of Hindu worship is approached through the angle of insularity, by confronting the cases of Guadeloupe, Reunion and Mauritius. Current exchanges between the Hindus of Guadeloupe and India, the countries of the southern Caribbean and the Mascarene Islands are leading to new ways of learning about plants and their uses. These exchanges led to the introduction of numerous plant species, which gradually spread to the gardens, as “Creole” Hindu practices came into contact with more globalised Brahmanical knowledge. The spread of plants and the transmission of knowledge at different times between India, the West Indies and the Mascarenes shaped a particular relationship with the garden, as a place of intimacy and the unfolding of a singular belonging to the world. My thesis investigates the processes of creolisation, through the space of the garden and Hindu places of worship, foregrounding temporality as the principal analytical lens.